Bimbingan Konseling Sosial Bagi Anak Putus Sekolah di Desa Naileu Provinsi Nusa Tenggara Timur - Yenry Pellondou; Selvin Sandra Ba'ik; Friandy Windisany Thoomaszen (SOLIDARITY: Journal of Social Studies, 2021)
The purpose of this study was to determine the extent of the counseling guidance function (social) for School Drop Outs, in the Naileu Village. Using qualitative research methods, the research informants were Guidance and Counseling Teachers and 3 school dropouts, with guidelines for observation, interviews, home visits, and documentation. The validity of the data is tested by triangulation. Data were analyzed using data reduction, data presentation, and verification. Thus, it was found that (1) children drop out of school due to lack of harmony in the household, the desire of children to be able to help parents to meet household needs, feelings of shame arising from the age of children over the age of their friends, and feeling lazy because of the distance between homes and schools that are far away and have a minimum public transportation. (2) In addition, in carrying out their duties, counseling guidance teachers are tasked with finding out the factors that cause children to drop out of school through home visit activities. After that the guidance teacher does guidance, guides parents and students to change the wrong mindset by providing motivation that education is important for the child's future. Tujuan penelitian ini untuk mengetahui sejauh mana Fungsi Bimbingan Konseling (sosial) bagi Anak Putus Sekolah, di Desa Naileu. Dengan menggunakan metode penelitian kualitatif, informan penelitian adalah guru bimbingan dan konseling dan 3 anak putus sekolah, dengan pedoman observasi, wawancara, home visit, dan dokumentasi. Keabsahan data diuji dengan triangulasi. Data dianalisis dengan menggunakan reduksi data, penyajian data, dan verifikasi. Maka, ditemukan bahwa (1) anak putus sekolah karena kurang keharmonisan dalam rumah tangga, keinginan anak agar bisa membantu orangtua demi memenuhi kebutuhan rumah tangga,  perasaan malu yang timbul akibat usia anak melebih usia teman-temannya, dan perasaan malas karena jarak antara rumah dan sekolah yang jauh serta miminya transportasi umum.(2) Selain itu dalam menjalankan tugasnya guru bimbingan konseling bertugas untuk mencari tahu faktor penyebab anak putus sekolah melalui kegiatan home visit. Setelah itu guru bimbingan melakukan bimbingan, menuntun orangtua dan siswa untuk mengubah pola pikir yang keliru dengan memberikan motivasi bahwa pendidikan penting bagi masa depan anak. Kata Kunci:Bimbingan dan Konseling Sosial, Anak Putus Sekolah.